Training anticipation for intermediate tennis players - Scott, D.; Scott, L. M.; Howe, B. L. (Behavior Modification, 1998)
The purpose of this study was to examine the trainability of anticipation in intermediate tennis players. In particular, the study examined whether video presentations could improve on-court tennis serve returns. A series of separate A-B designs across 6 participants was implemented, with baseline and intervention scores for on-court serve-return performance being recorded. Intervention consisted of 2 phases: a training phase and an on-court testing phase. The training phase, which employed a changing criterion design, consisted of a series of tennis-serve video presentations that were replayed with gradually increasing speed. All serves were occluded on racquet/ball contact, and participants were asked to predict the type, depth, and width of the serve. Following completion of the training phase, participants were again tested on their ability to return tennis serves on the tennis court. On-court results suggested that anticipation ability and performance did improve as a result of the intervention.